Loss of FGFR3 Delays Acute Myeloid Leukemogenesis by Programming Weakly Pathogenic CD117-Positive Leukemia Stem-Like Cells - Guo, Chen; Ran, Qiuju; Sun, Chun; Zhou, Tingting; Yang, Xi; Zhang, Jizhou; Pang, Shifeng; Xiao, Yechen (Frontiers in Pharmacology, 2021)
Chemotherapeutic patients with leukemia often relapse and produce drug resistance due to the existence of leukemia stem cells (LSCs). Fibroblast growth factor receptor 3 (FGFR3) signaling mediates drug resistance of LSCs in chronic myeloid leukemia (CML). However, the function of FGFR3 in acute myeloid leukemia (AML) is less understood. Here, we identified that loss of FGFR3 reprograms MLL-AF9 (MA)-driven murine AML cells into weakly pathogenic CD117+ positive leukemia stem-like cells by activating FGFR1-ERG signaling pathway. FGFR3 deletion significantly inhibits AML cells in vivo engraftment and extends the survival time of leukemic mice. FGFR3 deletion sharply decreased the expression of chemokines and the extended survival time in mice receiving FGFR3-deficient MA cells could be neutralized by overexpression of Ccl3. Here we firstly found a novel regulatory mechanism for FGFR3 in AML and provided a promising anti-leukemia approach by inhibiting FGFR3 functions.